Karakterisasi Aktivitas Fungsional Senyawa Bioaktif dari Whey Hasil Samping Produksi Tahu - Alfia Aretzy; Elvira Syamsir; Azis Boing Sitanggang (Jurnal Teknologi dan Industri Pangan, 2022)
Tofu whey is a by-product obtained during tofu production that contains proteins and peptides, soluble carbohydrates, soy isoflavone, and minerals. This research aimed to characterize the functional properties of whey protein from tofu through separation using membranes with different pore sizes. The permeate resulted from Whatman No. 3 filtration was subjected to acidity (pH) and protein content measurement, while its protein profile was characterized by SDS-PAGE. electrophoresis. Additionally, this permeate was further sieved using ultrafiltration membranes with 30, 10, and 5 kDa cut-off. The corresponding filtrates were analyzed for antioxidant activity, isoflavone content, and ACE inhibitor activity. The tofu whey had a pH of 3.14, crude protein of 2 g/100 g sample, and soluble protein content of 1.47mg/mL. The separation of protein bands using SDS-PAGE showed that the dominant protein or peptides in tofu whey had molecular weights below 18 kDa. The use of ultrafiltration membranes could increase the bioactivity of permeates. The filtrate resulting from the smallest membrane cut-off (i.e., 5 kDa) had a higher antioxidant activity, isoflavone content, and ACE inhibitory activity.